Kualitas Air dan Cemaran Logam Berat Merkuri (Hg) dan Timbal (Pb) pada Ikan Nila (Oreochromis niloticus) Hasil Tangkapan dari Waduk Tunggu Pampang Kota Makassar - Andi Santi; Muh. Ali Arsyad (Fapetrik-UMPAR, 2021)
The level of heavy metal contamination of mercury (Hg) and lead (Pb) in the aquatic ecosystem of the Waiting Pampang Reservoir, Makassar City, is known by determining the concentration of these heavy metals in water and biota (tilapia). Tilapia is a catch that is relatively abundant in the Waiting Pampang Reservoir. This study aimed to determine water quality and levels of Hg and Pb contamination in water and tilapia caught from the Waiting Pampang Reservoir. Water quality is determined by measuring 1) the degree of acidity (pH), 2) Dissolved oxygen (DO), 3) Biological oxygen demand (BOD), and 4) Chemical oxygen demand (COD). The results showed that the BOD and COD values had passed the threshold so that the waters of the Waiting Pampang Reservoir were contaminated with organic matter. However, it has not been contaminated with Hg and Pb (<0.001 mg/kg) heavy metals. Tilapia caught from the Waiting Pampang Reservoir contained heavy metal Pb, but the concentration was far below the permissible value. However, the consumption of tilapia from the Waiting Pampang Reservoir must still be watched out for because heavy metals are accumulative.